2021
DOI: 10.3389/fpls.2021.793876
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Study Supports the Role of Trehalose in Carbon Transfer From Fungi to Mycotrophic Orchid

Abstract: Orchids rely on mycorrhizal symbiosis, especially in the stage of mycoheterotrophic protocorms, which depend on carbon and energy supply from fungi. The transfer of carbon from fungi to orchids is well-documented, but the identity of compounds ensuring this transfer remains elusive. Some evidence has been obtained for the role of amino acids, but there is also vague and neglected evidence for the role of soluble carbohydrates, probably trehalose, which is an abundant fungal carbohydrate. We therefore focused o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 105 publications
(199 reference statements)
0
7
0
Order By: Relevance
“…Trehalose has been suggested as a fungi-derived carbon source for orchids; in Dactilorhiza majalis , the treatment by validamycin A (trehalase inhibitor) inhibited the growth of the protocorms infected with Ceratobasidium sp. [ 8 ]. In the Assembly 4, six contigs had high sequence similarity with the trehalase genes, and among them, read counts of three putative trehalase genes (evgLocus_101728.p1, evgLocus_593495.p1, and evgLocus_117844.p1) were highly detected in OM fungus-infected protocorms, but not in aseptically grown protocorms ( S2 Fig ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trehalose has been suggested as a fungi-derived carbon source for orchids; in Dactilorhiza majalis , the treatment by validamycin A (trehalase inhibitor) inhibited the growth of the protocorms infected with Ceratobasidium sp. [ 8 ]. In the Assembly 4, six contigs had high sequence similarity with the trehalase genes, and among them, read counts of three putative trehalase genes (evgLocus_101728.p1, evgLocus_593495.p1, and evgLocus_117844.p1) were highly detected in OM fungus-infected protocorms, but not in aseptically grown protocorms ( S2 Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…In order to evaluate the validity of the contig set constructed in this study and to get any insights about genes important for the interaction between orchids and OM fungi, we estimated gene expression levels in our protocorm samples using Assembly 4 contig set as a reference. Nodulin-like genes, CSGs and SWEET genes have been shown to have roles in mutualistic plant–fungus interactions [ 51 56 ], and recently, the trehalase gene has been suggested to be involved in mycoheterotrophy in orchids [ 8 , 9 ]. When estimated expression levels of these genes, they were expected to be upregulated in the protocorms grown with OM fungi compared to those in the aseptic condition ( S2 Fig ).…”
Section: Discussionmentioning
confidence: 99%
“…Kristiansen et al, 2001;Selosse et al, 2004;Cameron et al, 2006;Chang & Chou, 2007;Hobbie & H€ ogberg, 2012;Bougoure et al, 2014;Kuga et al, 2014;Suetsugu et al, 2017;Favre-Godal et al, 2020). Aside from soluble carbohydrates (Cameron et al, 2006;Ponert et al, 2021), amino acids, playing a significant role in N transfer, have been recognized to participate in C transfer in orchid mycorrhiza (Cameron et al, 2006(Cameron et al, , 2008Dearnaley & Cameron, 2017;Fochi et al, 2017;Favre-Godal et al, 2020;Valadares et al, 2021). Notably, fungal proteins and amino acids are enriched in 15 N by c. 10& relative to fungal chitin, irrespective of the part of the fungus examined (Taylor et al, 1997;Hobbie & Colpaert, 2003).…”
Section: Isotopic Signature Reveals Nutrient Exchange Function Of Roo...mentioning
confidence: 99%
“…Early experiments with radioactive tracers (see Smith & Read, 2008) showed that carbon is transferred to the plant before the pelotons extensively collapsed inside OrM protocorms, with early peaks of labeled trehalose and saccharose (Smith, 1967). Intriguingly, several orchid species can grow in vitro on trehalose as the sole sugar source, and Ponert et al (2021) reported in Dactylorhiza majalis an efficient trehalase-dependent metabolic pathway that enables orchids to utilize exogenous trehalose. Genomic data support this peculiar ability of orchids to utilize trehalose (Li et al, 2022), and transcriptomic data further suggest that trehalose may be transferred from the fungus to the plant because genes coding for plant trehalases are significantly upregulated in OrM protocorms (Ja z kalski et al, 2021;Chen et al, 2022) as well as in adult mycoheterotrophs (Li et al, 2022).…”
Section: Peloton Functioning In Nutrient Transfermentioning
confidence: 99%